Circular PVT1 promotes cardiac fibroblast activation interacting with miR-30a-5p and miR-125b-5p - Alessia Bibi; Alisia Madè; Simona Greco; Jose Manuel Garcia-Manteiga; Anna Sofia Tascini; Spyros Tastsoglou; Germana Zaccagnini; Przemyslaw Leszek; Carlo Gaetano; Fabio Martelli (Cell Death and Disease)
Abstract Circular RNAs (circRNAs) are involved in the pathogenesis of several cardiovascular diseases, including heart failure. In this study, we report that circular PVT1 (circPVT1) was upregulated in the left ventricle of 31 ischemic heart failure patients compared to 11 non-ischemic controls. RNA sequencing analysis following circPVT1 knockdown in immortalized human cardiomyocytes identified differentially expressed genes, mainly involved in fibrosis. Notably, in human cardiac fibroblasts, circPVT1 expression significantly increased after TGF-β1 treatment and circPVT1 silencing attenuated the levels of pro-fibrotic markers induced by TGF-β1. RNA pull-down assays validated the interaction between circPVT1 and two fibrosis-related miRNAs, miR-30a-5p and miR-125b-5p. The levels of these miRNAs were not altered upon circPVT1 knockdown. However, the expression of their mRNA targets was deregulated upon circPVT1 silencing, suggesting that circPVT1 modulates miRNA cellular bioavailability. Accordingly, inhibition of either miR-30a-5p or miR-125b-5p restored the expression of TGF-β1-induced pro-fibrotic markers following circPVT1 silencing, indicating that both miR-30a-5p and miR-125b-5p act as downstream effectors of circPVT1 in cardiac fibroblast activation. In conclusion, these findings highlight a pro-fibrotic role for circPVT1, which can regulate cardiac fibroblast activation interacting with the anti-fibrotic miR-30a-5p and miR-125b-5p. The modulation of circPVT1 expression may represent a potential strategy to reduce cardiac fibrosis and remodeling.